Determinants of exports in Zambia’s Manufacturing Sector - Mwiinga, Mwiinga (Research of GSB, 2019)
The cyclical price movements of primary products exported from Zambia has placed the country at a disadvantage. This stems mainly from the fact that lower prices of primary commodities have had negative effects on the balance of payments and the developmental agenda of the Zambian government. It is therefore important that efforts are made by the government to move towards supporting product sophistication, primarily focusing on the growth of industries that offer the greatest possible impact. In this regard, the growth of the manufacturing sector becomes of the utmost importance. This is mainly because the more the manufacturing sector is developed, the greater the technological transfer which will in turn facilitate product sophistication. This will also mitigate the dependency on exports of primary commodities such as copper, and make the economy less susceptible to cyclical price movements of primary commodities. It was therefore important that the study investigated the determinants of export performance in Zambia’s manufacturing sector. Variables analysed included Foreign Direct Investment (FDI), inflation rate, exchange rate, Gross Domestic Product (GDP) and lending rates. The study utilised the Ordinary Least Square (OLS) and the Auto Regressive Distributive Lag techniques to capture the dynamic relationships. The results revealed that Inflation and FDI were statistically significant. It was further observed that inflation was negatively related to exports in manufacturing sector. FDI, on the other hand, was positively related to exports in the manufacturing sector in the long run. GDP and lending rates were statistically insignificant, which could be as a result of the openness of the economy and low productive capacity. One of the key recommendations made was for government to effectively manage its policies in a way that maximises FDI inflows, whilst minimising inflation to effectively create a favourable macroeconomic environment for the sustained growth of the manufacturing sector. It was further observed that FDI, GDP and Inflation rate jointly affected exports in the manufacturing sector, therefore confirming that the three variables do have a joint effect on exports in the long run.